Pemetaan Habits of Mind Mahasiswa : Landasan untuk Pengembangan Strategi Pembelajaran Berbasis Inkuiri - Masiah Masiah; Siti Rabiatul Adawiyah; Lalu Jaswandi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Habits of Mind (HoM) is an important thinking disposition that supports successful learning in higher education, especially in inquiry-based learning. This study aims to map the profile of students' habits of mind as a basis for developing inquiry-based learning strategies. The study used a quantitative descriptive approach involving 60 students in semesters I, III, V, and VII. Data were collected through an online questionnaire containing 16 indicators of habits of mind based on the Costa and Kallick framework, then analyzed using percentage scores based on semester and indicator. The results showed that students' habits of mind achievement was in the good category, with the highest scores in semesters I (81%) and VII (80%), while semesters III and V were in the sufficient category (74%). Indicators with the highest scores included listening with understanding and empathy (90%), striving for accuracy (85%), and persisting (84%), while the lowest scores were found in thinking flexibly (62%), thinking interdependently (69%), and finding humor (71%). These findings indicate that students possess strengths in perseverance, thoroughness, and empathy, but still need to strengthen their thinking flexibility and collaboration. Therefore, structured and collaborative inquiry-based learning is recommended to develop students' habits of mind in a more balanced manner.